Innominate Artery Cannulation for Proximal Aortic Surgery - Mert,Bülent (2022)
ABSTRACT Introduction: The aim of this study was to evaluate the efficacy and safety of innominate artery cannulation strategy with side-graft technique in proximal aortic pathologies. Methods: A total of 70 patients underwent innominate artery cannulation with a side graft for surgery on the proximal aorta from 2012 to 2020. There were 46 men and 24 women with an average age of 56±13 years. The indications for surgery were type A aortic dissection in 17 patients (24.3%), aortic aneurysm in 52 patients (74.3%), and ascending aorta pseudoaneurysm in one patient (1.4%). The innominate artery was free of disease in all patients. Hypothermic circulatory arrest with antegrade cerebral perfusion was utilized in 60 patients (85.7%). Three patients had previous sternotomy (4.2%). The most common surgical procedure was ascending aorta with hemiarch replacement in 34 patients (48.5%). Results: The mean cardiac ischemia and cardiopulmonary bypass times were 116+46 minutes and 164+56 minutes, respectively. Mean antegrade cerebral perfusion time was 27+14 minutes. The patients were cooled between 22°C and 30°C during surgery. Thirty-day mortality rate was 7.1% (five patients). One patient (1.4%) had stroke, one patient (1.4%) had temporary neurologic deficit, and eight patients (11.4%) had confusion and agitation that resolved completely in all cases. There was no local complication or arterial injury. Conclusion: Cannulation of the innominate artery with side graft is safe and effective for both cardiopulmonary bypass and antegrade cerebral perfusion. This technique provides satisfactory neurologic outcomes for proximal aortic surgery.